A Modification of Fenestration Technique (MOFT) to Increase Vestibular Depth: A Case Series - Anukrati Katariya; Bhavna J. Kukreja (Indian Journal of Dental Research)
The most prevalent mucogingival issues include insufficient gingival width, decreased vestibular depth, abnormal frenal attachment, gingival recession, pockets that reach the mucogingival junction, excess gingival, inconsistent gingival margin, excessive gingival display and abnormal gingival colour. Numerous periodontal plastic operations have been used to treat these issues. However, each approach has its own drawbacks and is technique-dependent. Adequate depth of vestibule is necessary to maintain good oral health as shallow vestibule leads to accumulation of food and thus impedes oral hygiene maintenance. This case series describes a vestibular deepening procedure performed using modification of periosteal fenestration technique. This technique includes a series of eight cases of shallow vestibule where vestibular deepening was conducted by giving a full-thickness incision to expose the periosteum and create a window of fenestration followed by suturing the labial mucosa to the periosteum at the apical level. The results reported an excellent post-operative outcome showing increased depth of the vestibule.